(untitled) (Bangladesh Journal of Agricultural Research, 2008)
The study was conducted to evaluate the seasonal influence on in vivo pollen ermination, pollen viability, and pollen tube growth of lablab bean genotypes associated with poor pod setting beyond winter season. Four genotypes, namely IPSA Sheem-1, IPSA Sheem-2, BU Sheem-3, and JER were evaluated during September 2000 to December 2001 covering one main season (winter) and two off seasons (early) summer and late summer). Compared to off-seasons, all the genotypes performed better for all the parameters during winter. Every delay in planting was associated with appreciable reduction in pollinated stigma, in vivo pollen germination, pollen tube growth into style or ovary due to adverse effect of environmental factors. Stigma harvested at 8 to 12 hours after anthesis produced better results for most of the embryological parameters in winter. But for reaching the maximum level of pollination and fertilization beyond winter season, a period of 24 hours after anthesis was the safe limit. Bangladesh J. Agril. Res. 32(4) : 519-532